Implementasi Sistem Pemesanan Menu Di Kafe Dan Resto Sunny Bangkinang Menggunakan Qr Code Berbasis Website Menggunakan Framework Codeigniter - Anggun Dinda Putri Milenia; Fenty Kurnia Oktorina; Fina Nasari (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2024)
Currently, ordering menus at Sunny cafes and restaurants is still manual. Ordering menus that are still manual creates a problem, namely when the customer has finished selecting a menu, the customer does not know the total price of the order. Customers who come together at the same time will cause a buildup of order queues. From these problems, we get a solution by building a menu ordering system using a website-based QR Code using the PHP programming language, the CodeIgniter Framework, MySQL as a database and using UML (Unified Modeling Language) as a design. The purpose of making this system is so that customers can easily get information on menu catalogs and prices without having to ask the waiter. A menu ordering system at Sunny cafes and restaurants using QR codes has been successfully created.